Customer’s Loyalty Of Indonesia Cellular Operators: Roles Of User Experience, Satisfaction, Switching Barriers, And Corporate Image - Rachmawati, Indira (2019)
The telecommunications industry in Indonesia has grown rapidly since the issuance of the government regulation regarding the change of competition became an oligopoly. The increasing number of subscribers is getting stagnant along with the increasing high churn rate, decreasing customer growth and low average revenue per user that indicates a decline in loyalty. The present study developed a conceptual research framework for potential predictors of loyalty to cellular operators. The research framework was developed in light of an extensive literature review and expert opinions from academicians and practitioners. Cognition-to-action loyalty phase framework supports the established framework. The present study takes into consideration the cellular operator’s five dimensions of user experience, namely functionality, social, monetary, trustworthiness, and perceived service quality as independent variables. The variable of corporate image was considered as a moderating variable, the variables of satisfaction and switching barriers were considered as mediating variables, whereas the variable of loyalty was a dependent variable. A quantitative approach through a survey questionnaire was used to collect primary data in the three parts of Indonesia. Out of 400 cellular operator users surveyed in this study were collected through internet survey.